Studi pengembangan Sistem Jaringan Distribusi Air Bersih Perumahan Aloha ke Jl. Raya S. Parman Sidoarjo - Safitri, Mona Shinta; Zettyara, Devi (Jurnal Pendidikan Indonesia, 2025)
The fulfillment of the need for clean water is an important indicator of the level of quality of human life. The Sidoarjo Regency Government in collaboration with PT. East Java Clean Water through the Umbulan regional SPAM project to meet the community’s clean water needs. This study aims to analyze the planning of adding a clean water distribution pipeline network from Aloha Housing to Jl. Raya S. Parman using WaterCAD v8 hydraulic simulation. The research methodology includes population growth analysis using geometric methods, calculation of domestic and non-domestic water needs, and hydraulic simulation of piping systems. Population data was obtained from three villages, namely Pepelegi, Wage, and Sawotratap with a projection of the next 10 years. The results of the study show that the total water requirement is 88.75 lt/second to serve 54,753 residents. Hydraulic analysis using WaterCAD showed that the optimal pipe diameter was 300 mm with a residual pressure of 2 bar at the final junction. The simulation shows that the system is able to serve water needs at the minimum conditions, the first maximum (06.00), and the second maximum (18.00). This study provides technical recommendations for the development of effective and efficient clean water infrastructure in the study area.